(untitled) (Acta Horti Botanici Bucurestiensis, 2024)
In this paper, Acalypha rhomboidea (Euphorbiaceae) is reported for the first time, as a neophyte, in the vascular flora of Romania. We have identified small populations of this species native to North America, in the central area of the Iași city (north-eastern Romania), as a weed in a garden of ornamental plants, near the Palace of Culture. Most likely it has been introduced here accidentally, by importing contaminated growing medium for gardens. It produces viable seeds and seems to survive here for more than 10 years despite regular weed control. The morphology of this species is described based on field and herbarium specimens, and checked on literature data. The paper also includes some data on general distribution and favourite habitats of this species, as well as two identification keys.